The Relationship Between Maternal Knowledge Level and the Number of Pregnancy Check-Up Visits at the Grogol Petamburan Community Health Center - Kathleen Juanita Gunawan; I Wayan Sumandyasa; Shelly Fransiska; Ninik Wibawani; Jason Jason (Jurnal MedScientiae, 2023)
Antenatal care is the health service carried out by health workers to the mother during her pregnancy antenatal service standard compliance. When examined more deeply that the process of maternal death has a long journey so that prevention can be done since the antenatal care through education related to maternal health. Therefore, knowledge of pregnant women about antenatal care is very important because it will help reduce maternal and infant mortality .The purpose of this research is to know the relation of knowledge of mother with antenatal care number of visit of the Puskesmas Kecamatan Grogol Petamburan Jakarta Barat. This research conducted by method of cross sectional, the selection of samples with a consecutive sampling with 52 sample respondents. Data collection is carried out by filling a questionnaire made by researchers and is completed by respondents. Collected data is analyzed by chisquare test with significance level (⍺) 0.05. Stastical analysis.showed significant relationship between knowledge of antenatal care and the number of antenatal care visits (p=0,001)